KONSTRUKSI SOSIAL HAFIDZAH ALQUR'AN DI KABUPATEN JEMBER - Masykuroh, Wardatur Rochmah; Jannah, Raudlatul (Jurnal ENTITAS SOSIOLOGI, 2018)
Qur?an memorizer or commonly known as Hafidz Qur?an is currently getting quite intense attention from moslem society in Indonesia, especially moslem society in Jember. This positive acceptance can be seen from the development of tahfidz Qur?an program in various educational institutions in Jember and the number of educational scholarship offered to students who memorized Qur?an. This study aims to explain the social construction of the Hafidzah Qur?an in Jember with the use of constructivism method. The theory used is social construction that explains the formation of a society based on the knowledge they have through three simultaneous processes, namely, externalization, objectivation, and internalization. The result of this study is that the social construction of the moslem community in Jember shows positive acceptance of hafidzah Qur?an. It began with an externalizing moment when people found out about hafidz Qur?an through Islamic studies and television programs. Then the community formed the acceptance through the construction of tahfidz institution and the provision of scholarship to hafidz students in objectivation process, and finally it inspires the community to become hafidz and send their children to tahfidz institutions in the process of internalization.  Keywords: Hafidz Qur'an, social construction, externalization, objectivation, internalization